PENGARUH MEDIA KUBUS ANGKA TERHADAP PEMAHAMAN KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK PERMATA HATI KECAMATAN INUMAN - Sasmija, Nova; ', Zulkifli N; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to examine the effect of cube number media on the comprehension of the number concept in children aged 4-5 years. This research was conducted at TK Permata Hati, Sub-District of Inuman during April 2017. The research used experimental method that was one group pre-test post-test design with 15 samples (sample size was 15 children). The instrument type used in this study is using observation sheet to record the activities that occurred during the treatment. Based on hypothesis test results obtained there was the effect of cube number media on the comprehension of the number concept in children aged 4-5 years at TK Permata Hati, Inuman district. Obtained t count value was 23,367 with sig 0,000, because sig <0,05 hence can be concluded that there was influence of cube number media on the comprehension of the number concept in children. In Hypothesis test can be seent count = 23,367> t table = 2,145. cube number media on the comprehension of the number concept in children aged 4-5 years at TK Permata Hati, Inuman district of 66.66%.Keywords: Comprehension Numbers Concept, Cube Numbers Media